GSTT1null and rs156697 Polymorphism in GSTO2 Influence the Risk and Therapeutic Outcome of B-Acute Lymphoblastic Leukemia Patients - Baba, Shahid M.; Pandith, Arshad A.; Shah, Zafar A.; Geelani, Sajad A.; Bhat, Javid R.; Gul, Ayaz; Guru, Sameer A.; El-Serehy, Hamed A.; Koul, Abid M.; Mansoor, Sheikh (Frontiers in Oncology, 2021)
Introduction Glutathione S-transferase (GST) gene deletion or polymorphic sequence variations lead to decreased enzyme activity that influences susceptibility and response to chemotherapy in acute lymphoblastic leukemia (ALL). This case–control study investigated the association of GST gene polymorphisms with the etiology and therapeutic outcome of B-ALL among Kashmiri population. Methods A total of 300 individuals including 150 newly diagnosed B-ALL patients and an equal number of age and gender matched controls were genotyped for five GST gene polymorphisms by polymerase chain reaction–restriction fragment length polymorphism technique (PCR-RFLP) and multiplex PCR techniques. Results Higher frequency of GSTT1null, GSTO2-AG, and GSTO2-GG genotypes was observed in ALL cases compared to controls that associated significantly with ALL risk (GSTT1null: OR = 2.93, p = 0.0001; GSTO2-AG: OR = 2.58, p = 0.01; GSTO2-GG: OR = 3.13, p = 0.01). GSTM1, GSTP1, and GSTO1 SNPs showed no significant association (p > 0.05). Combined genotype analysis revealed significant association of GSTT1null/GSTM1null (OR = 4.11, p = 0.011) and GSTT1null/GSTP1-AG (OR = 4.93, p = 0.0003) with B-ALL susceptibility. Haplotype analysis of rs4925 and rs156697 revealed that carriers of CG haplotype had increased risk of B-ALL (p = 0.04). Kaplan–Meier plots revealed significantly inferior 3-year disease-free survival for GSTO2-GG carriers (p = 0.002). Multivariate analysis confirmed GSTO2-GG as an independent poor prognostic factor for DFS (HR = 4.5, p = 0.034). Among combined genotypes, only GSTT1null/GSTP1-AG associated significantly with poorer DFS rates (p = 0.032). Conclusion This study demonstrated that GSTT1null individually or in combination with GSTM1null and GSTP1-AG genotypes associated with increased B-ALL risk. Also, rs156697 variant genotypes (AG and GG) associated with B-ALL, whereas the GG genotype of rs156697 influenced the treatment outcome.